THE INDONESIAN TITANIUM DEPOSIT TYPES AND THEIR RESOURCES: THE ASPCETS FOR TITANIUM COMMODITY DEVELOPMENT - Tampubolon, Armin (Buletin Sumber Daya Geologi, 2013)
Indonesia has several Titanium deposit types: beach placer, alluvial and lateritic types. The source of Titanium minerals in beach placer is derived from Tertiary Volcanic Rocks.Theoccurence of alluvial Titanium deposit is closely associated with cassiterite (tin minerals) alluvial in Bangka-Belitung Islands. The source of Titanium minerals (ilmenite) are derived fromweathering on tin mineralization hosted in metamorphic and granitic rocks within uplifted morphology areas. Lateritic Titanium deposits are formed by lateritization process in association with bauxite and nickel in Riau, Kalimantan and Sulawesi Islands. The sources of Titanium are in granitic and metamorphic basement rocks.Java beach placer resources are quite big in tonnage, nearly 50 million tons in total, with significant TiO  contents ranging from 8.91 % to 3.17 %. Beach placer along the south shoreline of Java seems to indicate consistency in their mineralogical and genetic types with relativelyhomogenous in TiO  contents. Sumatra shows significant resources for lateritic Titanium deposit that is up to 107,800,859 tons with 0.5% to 15 % TiO . The quite interesting resources are indicated by very significant TiO average (15%) with the total of 19,243,757 tons of lateritic deposit type in Bintan Island, Riau,Sumatra.  The total resources of beach placer type deposits in Sumatra are much  lower than lateritic ones.Sulawesi has both beach placer and lateritic types where the interesting resources of this island are indicated by quite big resources and significant values in TiO  grades in North Sulawesi; the tonnage is up to 31,400,000 tons with TiO  content average is 9.85 %.  On the basis of resources and processing technologies, beach placer deposits in Sumatera, Java and Sulawesi are thought to have potentially economic significance. However, such available resources are needed to upgrade by performing detailed and systematic exploration.Government policies and environment concerns are important aspects for consideration in Titanium commodity development of this country.